Agency, discourses and practices in the Andean region: The welfare brotherhoods and the Holy See (16th-17th centuries) - Paz Nomey, José Luis (2021)
In the Andean region, the welfare confraternities played a fundamental role in caring for the sick and helping people to die well. With the arrival of the Europeans, new diseases also came in the West Indies whose pathogens were transmitted to the native population, thus triggering serious demographic breakdowns. In this context, throughout this article we will discuss aspects related to the discourses and practices between the Holy See and these confraternities with a welfare projection. We will also deal with the role of the agencies established by the confraternities before the Holy See in order to obtain favors and benefits for their member and associates. Finally, we will look at the nature of the welfare work carried out by these institutions and the different hospitals founded throughout the 16th and 17th centuries in the Andean region (Bolivia, Ecuador, and Peru).